Sheep enterprise budgets : beneficial planning tools within Agriwise Macedonia - Milevska, Jasmina (SLU/Dept. of Economics, 2010)
Generally in Macedonia keeping farm records and farm business planning is not often practiced like an ordinary activity in farming. Therefore one of the crucial things to do it is to comprise and continuously practice record keeping of farm data. The efficient and justified farm business planning should be based on farm records about the previous work of the farm, which will bring a structured approach for planning all the activities, as well as provide a good basis for attracting investors and creditors for the additional expansion of the business.